Optimization of underground open intermediary space comfort in TOD complexes: A case study of Chongqing, China - Lili, Dong; Yufeng, He; Xiang, Chen; Na, Cheng; Tao, Liu (Frontiers in Public Health, 2023)
Rapid urbanization drives social development, but at the same time brings sustainable development Rapid urbanization drives social development, but at the same time brings sustainable development advantages of expanding underground space and relieving urban traffic congestion. High quality TOD complexes with natural elements in the intermediary space have been considered as one of the important means to address sustainable urban development. Nevertheless, intermediary spaces in TOD complexes face various challenges, such as significant contradictory factors in their physical environment spaces. This study classifies the underground open intermediary space into four types according to the characteristics of TOD complexes. And for these four types'Cthe physical environment—generated by various influencing factors of planar geometric, three-dimensional geometric, and detailed construction elements—is simulated using a numerical simulation method based on a static Taguchi experiment. The results demonstrate that space shape is a primary influencing factor for luminous and thermal environments; the window-atrium ratio (W/A ratio) and hole-atrium ratio (H/A ratio) comprise contradictory factors between the luminous and thermal environments of these spaces; profile inclination angle and sunken plaza height are primary impact factors for the acoustic environment; and skylight type has minimal influence on the physical environment. On average, their luminous and acoustic environment comfort can be improved by 200%; whereas, their thermal environment comfort can be improved by 21% and the potential for optimizing it in their shallow space (underground space depth ≤ 10 m) is relatively low. Subsequently, the necessity of comfort optimization as the passive optimization design of underground open intermediary spaces' physical environment in TOD complexes in the future is discussed. Finally, the feasible path and prospect of how to improve the livability and comfort of the spatial physical environment of TOD complexes are discussed and prospected.